Analisis Pelanggaran Harapan Pertemanan Dian Dan Rian Di Web Series Setapak - Muhammad Denis Eka Putra; Afita Nur Hayati; Ida Suryani Wijaya; Muhammad Sali; Meilita Aulllia Putri (Institut Muslim Cendekia, 2025)
Web series is a popular and relevant digital series format for Generation Z. This study aims to analyze the Expectancy Violations Theory (EVT) phenomenon in the friendship dynamics of Dian and Rian in the Setapak web series, while also applying EVT to contemporary digital media narratives. This study uses a qualitative approach with a case study design. Data collection was conducted through in-depth content analysis of verbal and non-verbal interactions in Episode Two of the web series on YouTube, supplemented by unstructured interviews with the production team. Data were analyzed using Thematic Analysis. The results of the study indicate that a negative expectancy violation occurred in the episode. This violation was triggered by Rian's job offer at a photocopy shop to Dian after her graduation, which Dian perceived as an act of belittling her competence and bachelor's degree. These findings specifically confirm three core EVT: Dian's higher career expectations, negative Violation Valence, and a decrease in Rian's Communicator Reward Valence. Setapak successfully reflects how misalignment of assessments of individual aspirations can trigger significant conflict in Generation Z friendships. This study emphasizes the importance of empathetic communication and support for personal goals as the foundation of harmonious relationships